3D Spatiotemporal Mechanical Microenvironment: A Hydrogel‐Based Platform for Guiding Stem Cell Fate. Issue 49 (31st July 2018) - Ma, Yufei; Lin, Min; Huang, Guoyou; Li, Yuhui; Wang, Shuqi; Bai, Guiqin; Lu, Tian Jian; Xu, Feng
Abstract: Stem cells hold great promise for widespread biomedical applications, for which stem cell fate needs to be well tailored. Besides biochemical cues, accumulating evidence has demonstrated that spatiotemporal biophysical cues (especially mechanical cues) imposed by cell microenvironments also critically impact on the stem cell fate. As such, various biomaterials, especially hydrogels due to their tunable physicochemical properties and advanced fabrication approaches, are developed to spatiotemporally manipulate biophysical cues in vitro so as to recapitulate the 3D mechanical microenvironment where stem cells reside in vivo. Here, the main mechanical cues that stem cells experience in their native microenvironment are summarized. Then, recent advances in the design of hydrogel materials with spatiotemporally tunable mechanical properties for engineering 3D the spatiotemporal mechanical microenvironment of stem cells are highlighted. These in vitro engineered spatiotemporal mechanical microenvironments are crucial for guiding stem cell fate and their potential biomedical applications are subsequently discussed. Finally, the challenges and future perspectives are presented. Abstract : Engineering of 3D spatiotemporal mechanical microenvironments based on novel hydrogels is reviewed. These in vitro engineered spatiotemporal mechanical microenvironments (e.g., spatially heterogeneous and temporally dynamic mechanical cues) are crucial for guiding stem cell fate, and their potential biomedical applications including stem‐cell‐based therapy, pathological study, tissue engineering, and organoid formation are subsequently discussed.